The marketing research project manual - Jarboe, Glen R. (Cincinnati : South-Western College, 1999)
This book is about: The marketing research project; Market segmentation, positioning, and customer satisfaction studies; Choosing a topic and working with a client; ...
Keywords: Marketing; Methodology; Marketing research -- Methodology -- Handbooks, manuals, etc; Market surveys -- Methodology -- Handbooks, manuals, etc